Energy resources : availability, management, and environmental impacts - Skipka, Kenneth J; Theodore, Louis (Boca Raton : CRC Press, Taylor & Francis Group, 2014)
'This book provides an evaluation for each of the current means and consumption of power generation of the available fuel resources. The book examines resource quantity, resource availability, economics, energy quality, conservation requirements, transportation requirements, delivery requirements, operation and manufacturing, regulatory issues, political issues, environmental concerns, cost consequences, advantages, disadvantages, and public acceptance. It defines the energy issues of availability and management, and provides a means of solving energy problems as well as defining the optimal course for the future.'--
'Over the past several decades, there has arisen among informed leaders of industry, government and the environmental movement, an acute awareness of energy as a problem of impending critical magnitude on the national and international scene. The energy crisis or problem, as it has been called, was created by historical increases in demand for energy and the continuing lack of a viable management policy. This situation has resulted in two issues that are fast becoming pervasive concerns. One is the adequate, reliable supply of all forms of energy in developed countries, and the other is the growing public concern with the environmental and social consequences of producing and distributing usable energy'--
Includes bibliographical references and index.
Keywords: Power resources